Comparative Study of the CSR Initiatives of Microsoft, IBM, Google, Sun Microsystems and Cisco Systems in the Gulf Region - Nedumparambu Mana, Ravi Krishnan (2008)
CSR is one of the most relevant topics when it comes to today’s business environment. There are many studies and researches going in terms of different aspects of CSR and how it leads to business sustainability. The management project “Comparative Study of the CSR Initiatives of Microsoft, IBM, Google, Sun Microsystems and Cisco Systems in the Gulf Region” is another research project which is done in the area of CSR and an emerging region. Our project focuses on five main firms in the ICT industry and analyses their CSR initiatives in the region. It also studies how the firms can improve on their practices by taking CSR as a strategic tool to create economic, social and environmental benefits. This individual report is a part of group management report which discuses the role and contribution of each person in completing the group project and our perspective of the journey of the project. In my individual report I have talked about how the project was bloomed and how we as a team worked on it and concluded the report. I have also talked about different important situations and issues we had during this journey. Finally the report ends with my personal note about what I have gained through this report.